2017
DOI: 10.3390/su9112059
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency and Its Driving Factors in China’s Three Economic Regions

Abstract: Abstract:Energy efficiency improvement is essential for China's sustainable development of its social economy. Based on the provincial panel data of China's three economic regions from 1990 to 2013, this research uses the data envelopment analysis (DEA) model to measure the total-factor energy efficiency, and the Tobit regression model to explore the driving factors of efficiency changes. Empirical results show: (1) Energy efficiency, energy consumption structure, and government fiscal scale are significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…However, temperature change showed a negative relationship with profit efficiency (Tables 2–4). The estimation outcomes are consistent with the studies of Fleiter et al (2012), Filippini et al (2014); and Shi et al (2017). Major economic activities in the EU are powered by fossil fuels and other non-RESs such as coal and nuclear.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, temperature change showed a negative relationship with profit efficiency (Tables 2–4). The estimation outcomes are consistent with the studies of Fleiter et al (2012), Filippini et al (2014); and Shi et al (2017). Major economic activities in the EU are powered by fossil fuels and other non-RESs such as coal and nuclear.…”
Section: Discussionsupporting
confidence: 84%
“…It suggested that the difference between x * and x o and y * and y o pointed at the need for managerial improvement (Cooper et al , 2000). In this section, the authors evaluate how well economic variables are enhancing the profit efficiency of the bioenergy industry in the EU28 region following the models from prior studies (Martínez, 2013; Filippini et al , 2014; Filipović et al , 2015; Flues et al , 2015; Shi et al , 2017). The following equation (3) is based on a balanced panel data for observed countries EU28 ( i = 1,…, 28) during the period 1990–2013 ( t = 1,…,24): …”
Section: Methodsmentioning
confidence: 99%
“…They stated that influencing factors have various impacts on the carbon emission efficiency in the Chinese regions [53]. Some other scholars also investigated the carbon emission efficiency by using Tobit studies recently [54][55][56].…”
Section: Literature Reviewmentioning
confidence: 99%
“…When multiplying the energy input by (1-θ), we can obtain the radial adjustment, which is a measure of energy saving. Recently, a number of extended studies have been based on the DEA method (such as [24][25][26][27][28][29][30][31]).…”
Section: Energy-economic-efficiency-estimatementioning
confidence: 99%